School sites and the haunting of history: unmasking the past in field-based research. Issue 9 (21st October 2021) - Ferguson, Daniel E.; Nichols, T. Philip
Abstract: In field-based research, masking practices, as well as the general practice of relegating historical context to abstracted 'site descriptions' in a paper's methodology section, can produce a tacit inattention to historical specificity. By juxtaposing two case studies of schools, this article examines the ways school sites are haunted by histories—that is, how the past is revived and revised in the present, and in turn what this means for field-based qualitative inquiry. Pairing archival and field-based methods, we trace how the haunting of history animated the present-day practices of stakeholders in two schools. In doing so, we show how history itself became an actor in these sites—as something administrators and teachers put to work in their approaches to schooling—and suggest expanding views of unmasking within qualitative inquiry that allow for these ghosts of the past to announce themselves more openly.